Determination of Ethanol Concentration in Kombucha Beverages: Single-Laboratory Validation of an Enzymatic Method, First Action Method 2019.08. (26th September 2020) - Ivory, Ruth; Delaney, Elaine; Mangan, David; McCleary, Barry V
Abstract: Kombucha is a fermented, lightly effervescent sweetened black or green tea drink. It is marketed as a functional beverage based on its proposed health benefits. Kombucha is produced by fermenting tea using a "symbiotic colony of bacteria and yeast" (SCOBY). Kombucha is marketed as a non-alcoholic beverage, however due to the production process employed, there is a high possibility that the Kombucha products will contain low levels of ethanol. Kombucha is sold in a raw and unpasteurized form and, if kept at temperatures above 4 °C, the possibility exists that it will continue to ferment, producing ethanol. This possibility of continued fermentation may lead to an increase in ethanol content from levels below 0.5%ABV at time of production to higher levels at time of consumption. Thus, there is a potential for levels rising to greater than 0.5%ABV, the threshold for certification as a non-alcoholic beverage. It is essential that Kombucha manufacturers have the capacity to accurately and quickly test for ethanol in their products.  The Ethanol Assay Kit is an enzymatic test kit developed by Megazyme for the determination of ethanol in a variety of samples. The kit has been validated in a single laboratory for use with Kombucha fermented drinks, fruit juices, and low-alcohol beer samples. The commercially available Ethanol Assay Kit (Megazyme catalogue no. K-ETOH) contains all components required for the analysis. Quantification is based on the oxidation of ethanol to acetaldehyde by alcohol dehydrogenase and further oxidation of acetaldehyde by acetaldehyde dehydrogenase with conversion of NAD + to NADH. The single laboratory validation (SLV) outlined in this document was performed on a sample set of eight different commercial Kombucha products purchased in Ireland, a set of five Cerilliant aqueous ethanol solutions, two BCR low-alcohol beer reference materials, two alcohol-free beer samples, and two fruit juice samples against SMPR 2016.001 (1). Parameters examined during the validation included Working range, Selectivity, Limit of Detection (LOD), Limit of Quantification (LOQ), Trueness (bias), Precision (reproducibility and repeatability), Robustness, and Stability. The Ethanol Assay is a robust, quick and easy method for the measurement of ethanol in Kombucha. Our data suggests this method is also reliable for similar matrices, such as low-alcohol beer and fruit juice. The assay meets all requirements set out in in AOAC SMPR 2016.001.